GENDER EQUALITY IN EDUCATION: Analysis of Rohana Kudus of Thought and Its Relevance to The Quran Surah At-Taubah Verse 71 - Hermansyah Lbs, Freddy; Ritonga, Arip Rachman; Salsabilah, Ismi; Hasanah, Huswatul (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to examine the relevance of Rohana Kudus' thoughts on women's education in the perspective of Islamic teachings, focusing on the interpretation of the Qur'an surah At-Taubah verse 7. Rohana Kudus is known as a pioneering female figure of the press and education in Indonesia who has a progressive view of the importance of women's role in social life, especially through education. This research uses a qualitative approach with the library research method, relying on primary and secondary sources such as biographies, scientific articles, historical documents, and the study of Qur'an interpretation. The analysis is carried out through a phenomenological approach to uncover the deepest meaning of Rohana Kudus thought in the context of Islamic values that uphold science, gender equality, and the glory of women. The results of the study show that the idea of Rohana Kudus is in line with Islamic principles, where education is seen as a fundamental right for all humanity, including women. She emphasized women’s emancipation through knowledge access. This view affirms that Islam is not a religion that restricts women, but rather encourages their active participation in nation-building. This finding confirms the importance of reviving the spirit of struggle of women figures like Rohana Kudus in the context of today's women's education.